"دور الإفصاح القطاعي في تعزيز ملائمة التقارير المالية" "دراسة تطبيقية على البنوك المدرجة في سوق دمشق للأوراق المالية" (Latakia University Journal - Economic and Legal Sciences Series, 2016)
هدف هذا البحث بصفة أساسية إلى بيان دور الإفصاح القطاعي في تعزيز ملائمة التقارير المالية, وذلك من خلال بيان دور المعلومات القطاعية في تعزيز القدرة على التنبؤ بالسعر السوقي للسهم, وبحصة السهم من التدفقات النقدية التشغيلية المستقبلية.لتحقيق ذلك, قُسَم البحث إلى جزأين: نظري وتطبيقي, تناول الباحث في الجزء الأول مفهوم الإفصاح القطاعي وطبيعة المعلومات التي يوفرها حول المنشأة وطرق تقسيم المنشأة إلى قطاعات, وبيان مفهوم ملائمة التقارير المالية, والخصائص التي تجعل التقارير المالية ملائمة لاحتياجات المستخدمين, ومن ثم بيان أهمية المحتوى المعلوماتي للإفصاح القطاعي في تعزيز ملائمة التقارير المالية.أما في الجزء الثاني فقد تم استخدام نموذج الانحدار الخطي(Linear Regression)لدراسة وتحليل نوع وقوة العلاقة بين متغيرات الدراسة والمتمثلة بـحصة السهم من نتائج أعمال القطاعات التشغيلية المكونة للبنوك المدرجة في سوق دمشق للأوراق كمتغيرات مستقلة, والسعر السوقي للسهم و حصة السهم من التدفقات النقدية التشغيلية المستقبلية كمتغيرات تابعة, وذلك بالتطبيق على عينة مكونة من (12) بنك مدرج في سوق دمشق للأوراق المالية تتوفر عنها البيانات اللازمة لإعداد الدراسة التطبيقية.أكدت النتائج صحة الفرضية الأولى القائلة: "يساعد الإفصاح عن نتائج أعمال القطاعات التشغيلية المكونة للمنشأة في التنبؤ بالسعر السوقي للسهم", كما أكدت صحة الفرضية الثانية القائلة: "يساعد الإفصاح عن نتائج أعمال القطاعات التشغيلية المكونة للمنشأة في التنبؤ بحصة السهم من التدفقات النقدية التشغيلية المستقبلية", الأمر الذي يؤكد صحة الفرضية الرئيسية للبحث القائلة: "يساعد الإفصاح عن المعلومات المتعلقة بالقطاعات التشغيلية المكونة للمنشأة في تعزيز ملائمة التقارير المالية".The objective of this research is primarily to indicate the role of the segmentdisclosure instrengthen the relevance of financial reports, through the statement of the role of the segmentinformation in enhance the ability to predict the market price of the shares, and the stockshare of future operating cash flows. To achieve this, the search is divided into two parts: theoretical and practical, the first part, is about the concept of segment disclosure and the nature of the information provided about the facility and ways to divide the property into segments, and indicate theconcept ofrelevance financial reports, and the characteristics that make the financial reports, relevance to the needs of users, and then show the importance informational content segment disclosure in promoting therelevanceof financial reports.In the second part has been used linear regression model (Linear Regression) to study and analyze the type and strength of the relationship between the variables of the study, of the results of the operating segmentsper share, consisting of banks listed on the Damascus Stock Exchange as Independent variables, and the market price of shares and per share from operating cash flows future as dependent variables, and that the application to a sample of (12) listed bank in Damascus Securities Exchange for the preparation of Applied study data are available.Results confirmed the health of the first hypothesis: "disclose of the results of the operating segments consisting of the facilityhelps to predict the market price per share", also confirmedThe health of the second hypothesis: "disclose of the results of the operating segments consisting of the facilityhelps to predict the share of the stock of future operatingcash flows ", which confirms the correctness of the main premise of the search theory: "disclosure of information relating to operating segments consisting of the facilityhelps instrengthentherelevance of financial reports".